Desenvolvimento de nanocápsulas poliméricas com diferentes revestimentos para a liberação cerebral de vimpocetina - De Marco, Maria Gilda (2018)
Vinpocetine (VP) is used in neurodegenerative diseases, and researches have indicated a promising anticonvulsant effect of this drug. However, it shows some limitations as low aqueous solubility and short half-life. Polymeric nanoparticulate systems are described in the literature as alternatives to increase the solubility of substances and to promote controlled release of drugs, as well as these systems are able to improve the brain delivery of active molecules. The objective of this study was to develop biodegradable poly(ɛ-caprolactone) (PCL Mn 10,000) nanocapsules (NCs), with different coatings, for cerebral delivery of vinpocetine, evaluating the physico-chemical characteristics, the ability for the control drug release and the alteration or not of the permeability/integrity of the blood-brain barrier (BHE) intercellular junctions. NCs were obtained by the interfacial deposition of preformed polymer (n = 3) and the formulations were defined according to their coatings/ stabilizers (polysorbate 80 (NCs-VP-P80), polysorbate 80 and polyethylene glycol 4000 (NCs-VP P80/P4000) or polysorbate 80 and polyethylene glycol 6000 (NCs-VP-P80/P6000)]. NCs presented a submicrometric size (around 200 nm, Zetasizer®), narrow size distribution (IPd <0.11), negative zeta potential, vinpocetine content near to the theoretical value (96-98%) and high encapsulation efficiency (EE> 99%). The nanometric size was confirmed by laser diffraction analysis. The type of coating of the NCs significantly influenced the relative viscosity of these systems (p <0.05), determined by capillary viscometer. The NCs suspensions were stable for 60 days after the preparation, with reduction in the drug content and significant increasing in the particle size after 90 days of storage, without influence of the presence or not of PEG. In vitro release from the NCs was performed using dialysis bags and phosphate buffer pH 7.4/ethanol (70:30 v/v) as medium. These structures were able to control release of vinpocetine in comparison to the free drug, without burst effect, and the release kinetics were not affected by the presence of PEG or its molecular weight. However, PEG influenced the mechanism of vinpocetine release. The nanocapsules presented spherical morphology and colloidal size, when analyzed by scanning electron microscopy, after lyophilization of the systems using trehalose (10% w/v). In the in vivo study, BHB integrity in mice was evaluated intraperitoneally using sodium fluorescein as the opening marker, because it does not cross entire BHB. The results showed that there was no significant difference (p> 0.05) between the treatment with the NCs containing or not the drug in relation to the controls (free vinpocetine and saline), considering the brain/blood ratio of fluorescein concentration. Thus, these systems did not promote alteration or disfunction in BHB, according to this study, being a sign of safety. In this sense, the developed PCL NCs are promising systems for the cerebral delivery of vinpocetine, with a view to the future treatment of neurological disorders, such as epilepsy.